Quantifying predator dependence in the functional response of generalist predators. (7th May 2017) - Novak, Mark; Wolf, Christopher; Coblentz, Kyle E.; Shepard, Isaac D.
Abstract: A long‐standing debate concerns how functional responses are best described. Theory suggests that ratio dependence is consistent with many food web patterns left unexplained by the simplest prey‐dependent models. However, for logistical reasons, ratio dependence and predator dependence more generally have seen infrequent empirical evaluation and then only so in specialist predators, which are rare in nature. Here we develop an approach to simultaneously estimate the prey‐specific attack rates and predator‐specific interference (facilitation) rates of predators interacting with arbitrary numbers of prey and predator species in the field. We apply the approach to surveys and experiments involving two intertidal whelks and their full suite of potential prey. Our study provides strong evidence for predator dependence that is poorly described by the ratio dependent model over manipulated and natural ranges of species abundances. It also indicates how, for generalist predators, even the qualitative nature of predator dependence can be prey‐specific.